Workshop Lesson study Bagi Guru Sekolah Dasar Di Sekolah Dasar Islam Terpadu Annida Lubuklinggau - Anna Fauziah; Maria Luthfiana (Yayasan Riset dan Pengembangan Intelektual, 2022)
Among the efforts to improve teacher professionalism is through lesson study. Lesson study is a model for developing teacher professionalism which has four main steps in the form of a Plan-Do-See-Redesign cycle which aims to produce learning device designs that are made collaboratively, carry out learning, observe learning to see the advantages and disadvantages of implementing learning. The purpose of this activity is to improve the competence of teachers through the lesson study system. The subjects in this activity were the teachers of Annida Lubuklinggau Integrated Islamic Elementary School. The method used is lecture and practice. Data was collected based on the results of documentation, observation, questionnaires and interviews. The results of the implementation of community service show that socialization and lesson study assistance to SDIT Annida Lubuklinggau teachers can increase the competency and motivation of SDIT Annida Lubuklinggau teachers to apply lesson study to the learning process in class.